Use the table below to answer this question:
x y
-1 -3
0 -1
2 3

Find the average rate of change for the given function from x = −1 to x = 2.

A.) −2

B.)−1

C.)1

D.) 2

Respuesta :

Given:

The table of values.

To find:

The average rate of change for the given function from x = −1 to x = 2.

Solution:

From the given table it is clear that y=-3 at x=-1 and y=3 at x=2.

Formula for average rate of change is

[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]

Using the above formula, the average rate of change for the given function from x = −1 to x = 2 is

[tex]m=\dfrac{3-(-3)}{2-(-1)}[/tex]

[tex]m=\dfrac{3+3}{2+1}[/tex]

[tex]m=\dfrac{6}{3}[/tex]

[tex]m=2[/tex]

Therefore, the correct option is D.

ACCESS MORE